Influence of high quality properties on productivity and quality of soft winter wheat grain - Жемела, Г. П.; Кузнецова, О. А. (Scientific Progress & Innovations, 2012)
Influence of high quality properties on elements of the productivity structure (quantity of productive stalks, number of grains in an ear, weight of grains from an ear, weight of 1000 grains) and forming soft winter wheat productivity has been investigated. It has been established that the greatest quantity of productive stalks, number of grains in an ear, weight of grains from it and also weight of 1000 grains of the varieties formed in the conditions of 2011. According to all indices of structure elements of productivity the variety Kolomak 5 was the best. Influence of variety on productivity is 20– 25 %.